The Effects of Government Internal Control Systems and Technology Utilization on The Financial Statement Quality of Local Government - Mardiana Mardiana; Ilham Rahim (Jurnal Manajemen Bisnis, 2022)
The purpose of this research is to examine the impact of the internal control system and the usage of information technology on the quality of local government financial reports (a survey on regional working units of Tolitoli regency). This is a quantitative study. The data used are original data gathered by delivering questionnaires to 13 Regional Working Units (RWU) that generate local revenue in Tolitoli Regency; each RWU is represented by three respondents, for a total of 39 respondents. The data was analyzed using multiple linear regression with the Statistical Product and Service Solutions application. The findings revealed that the internal control system and the application of information technology had a significant partial or simultaneous effect on the quality of the Tolitoli district government's financial reports.